2011
DOI: 10.1074/mcp.m110.001131
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Profiling of Madin-Darby Canine Kidney Plasma Membranes Reveals Wnt-5a Involvement during Oncogenic H-Ras/TGF-β-mediated Epithelial-Mesenchymal Transition

Abstract: Epithelial-mesenchymal transition (EMT) describes a process whereby polarized epithelial cells with restricted migration transform into elongated spindle-shaped mesenchymal cells with enhanced motility and invasiveness. Although there are some molecular markers for this process, including the down-regulation of E-cadherin, our understanding of plasma membrane (PM) and associated proteins involved in EMT is limited. To specifically explore molecular alterations occurring at the PM, we used the cationic colloida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 82 publications
4
33
0
Order By: Relevance
“…As exosomes are of endosomal origin they typically contain proteins involved in multivesicular body (MVB) biogenesis, membrane transport and fusion (e.g., RabGTPases) [66], tetraspanins and their associated proteins that are functionally organised into tetraspanin-enriched microdomains -also referred to as the tetraspanin web [67], and proteins that may be involved in downstream exosome recognition and internalisation in a recipient cell [68]. Proteome profiling using mass spectrometry and label-free spectral counting [63] was employed to determine enrichment of these protein classes in the three purification methods studied.…”
Section: Resultsmentioning
confidence: 99%
“…As exosomes are of endosomal origin they typically contain proteins involved in multivesicular body (MVB) biogenesis, membrane transport and fusion (e.g., RabGTPases) [66], tetraspanins and their associated proteins that are functionally organised into tetraspanin-enriched microdomains -also referred to as the tetraspanin web [67], and proteins that may be involved in downstream exosome recognition and internalisation in a recipient cell [68]. Proteome profiling using mass spectrometry and label-free spectral counting [63] was employed to determine enrichment of these protein classes in the three purification methods studied.…”
Section: Resultsmentioning
confidence: 99%
“…2003). More recently, it has been shown that expression of Wnt5a and collagen triple helix repeat‐containing protein 1 (Cthrc1) is highly up‐regulated during oncogenic H‐Ras/TGF‐β‐induced EMT of MDCK cells (Chen et al. 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous report showing that expression of Wnt5a is up-regulated during Snail-mediated EMT of A431 cells . More recently, it has been shown that expres- sion of Wnt5a and collagen triple helix repeat-containing protein 1 (Cthrc1) is highly up-regulated during oncogenic H-Ras ⁄ TGF-b-induced EMT of MDCK cells (Chen et al 2010). Cthrc1 can associate with multiple Wnt and Frizzled proteins as well as Ror2 and enhance the complex formation of Wnt-Frizzled-Ror2, thereby activating planar cell polarity (PCP) pathway selectively (Yamamoto et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The β-catenin–independent Wnt pathway behaves as a double-edged sword; it suppresses tumorigenesis in normal epithelium and in early tumors, but also serves as a critical driver of epithelial-mesenchymal transition [EMT] and cancer invasion (17–27). We recently defined a novel paradigm in Wnt signaling in which Frizzled receptors (FZDs) activate the G proteins and trigger non-canonical Wnt signaling via Daple (CCDC88C), which is a Dishevelled (Dvl)-binding protein (28).…”
Section: Introductionmentioning
confidence: 99%